Synthesis, Characterization and Anticancer Activity of Chitosan Schiff Base / PVP Gold Nano Composite in Treating Esophageal Cancer Cell Line - Maha A. Younus; Baker F. Abdallaha (مجلة بغداد للعلوم)
In the present paper, chitosan Schiff base has been synthesized from chitosan’s reaction with the salicyldehyde. The AuNPs was manufacture by extract of onion peels as a reducing agent. The Au NPs that have been prepared were characterized through the UV-vis spectroscopy, XRD analyses and SEM microscopy. The polymer blends of the chitosan Schiff base / PVP has been prepared through using the approach of solution casting. Chitosan Schiff base / PVP Au nano-composites was prepared. Nano composites and polymer blends have been characterized by FTIR which confirm the formation of Schiff base by revealing a new band of absorption at 1651cm-1 as a result of the (C=N) imine group. SEM, DSC and TGA confirms the thermal stability of the prepared polymer blends and nanocomposites, nano composites have shown good results in inhibiting esophageal cancer cell lines, IC50 of nanocomposite = 21.56 µg / mL.